Brexit Barrow: Real-Time Receptions of the Bible during a Summer of Political Chaos (Relegere: Studies in Religion and Reception, 2016)
In the wake of the 2008 recession, the first mainstream challenges to the dominance of neoliberalism and its accompanying Bible in English political discourse have emerged in the 2010s. The referendum on EU membership brought to the fore grievances that had been building for decades, particularly in towns that have faced sharp industrial decline. One such town is Barrow-in-Furness. This article analyses interviews, discussions, and social media activity during the Referendum campaign and its aftermath in order to see what kinds of perceptions about the Bible and religion exist in Barrow and to compare them with assumptions about the Bible and religion in mainstream political discourse. There was minimal interest in the Bible and regular ridicule aimed at political claims of the Bible as the source of English or British values and identity. This partly coheres with some recent research on understandings of Christianity but it must also be understood in the context of the hatred towards political and economic authority in places like Barrow. Despite the minimal interest in the Bible and Christianity, their commonly constructed Other—Islam—was regularly seen as another source of threatening authority, a telling fear in a town with only 0.2% identifying as Muslim.